PENGARUH PEMASANGAN MEDIA INTERPRETATIF TERHADAP PERUBAHAN PERILAKU WISATAWAN DALAM MEMBUANG SAMPAH DI TEBING BREKSI - Halim Ahmad; Bayu Grendo Sigarete (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Breksi Cliffs were built and managed for tourist destinations in 2015. One of the challenges in the management of tourism in Breksi Cliff is garbage. The main factor ignoring garbage problems by tourists is due to their poor understanding of the environment and the dangers of environmental damage. So that, we need an initiative from the manager of Breksi Cliff in managing the environment around the tourist site through the installation of an interpretive media that is educative to the tourists about the environment, as well as an effort to provoke tourists to participate actively in order to control garbage in Breksi Cliffs. This research is a qualitative research and it is using experimental method. The study design was randomized complete design with 2 treatments and 3 repetitions. The data were collected by sampling method, by counting the trash in 2x2 m area around the sampling points. The data collection is 6 times with 3 times data retrieval before treatment and 3 times data after interpretative media installation treatment. The result of research based on statistical analysis shows that there is real difference of amount of gaebage before and after installation of interpretative media, where the garbage quantity decrease from 13,4 to 4,1.Keywords: Breksi Cliff, Interpretative Media, Garbage, Experimental